2018
DOI: 10.1061/(asce)st.1943-541x.0002124
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive FE Study of the Hysteretic Behavior of Steel–Concrete Composite and Noncomposite RWS Beam-to-Column Connections

Abstract: This paper investigates the behaviour of reduced web section (RWS) steel-concrete composite (SCC) beam-to-column connections with circular web openings through a comprehensive finite element (FE) analysis following experimental and computational studies.Results showed that the presence of a circular web opening is effective to move the plastic hinge away from the column shear panel zone and the main connection components, and hence, significantly improve the ductility and energy dissipation of the connection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
(22 reference statements)
5
17
1
Order By: Relevance
“…In models with high composite action, the difference was smaller than expected and previously observed in the study of Shaheen et. al [2] -for welded connections, being no higher than 2.8% in this study. This small reduction was attributed to firstly, Vierendeel mechanism, which led to symmetric behaviours in positive and negative directions.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In models with high composite action, the difference was smaller than expected and previously observed in the study of Shaheen et. al [2] -for welded connections, being no higher than 2.8% in this study. This small reduction was attributed to firstly, Vierendeel mechanism, which led to symmetric behaviours in positive and negative directions.…”
Section: Discussioncontrasting
confidence: 44%
“…However, the literature review revealed the lack of experimental and FE studies of steel-concrete composite RWS connections. The only one exists [2] showed that composite action should be considered and confirmed the contribution of composite action in the overall strength capacity of the connection as well as its effect on the RWS connection. Consequently, the aim of this paper is to develop a comprehensive parametric FE study to analyse the effect of the degree of composite action on the performance of steel-concrete composite bolted extended end-plate (BEEP) RWS connections subjected to cyclic loads with positive and negative bending moments.…”
Section: Reduced Web Section (Rws) Connectionsmentioning
confidence: 84%
“…When experiencing the DBE, FWFP can reduce the structural failure probability many times over, while FRWS has a higher risk of damage at LS1-LS3 than FWUF overall. However, it is worth noting that the calculated negative load carrying capacity of the RWS connection tends to be conservative when the steel-concrete composite effect is neglected (Shaheen et al, 2018). Perhaps in a steel-concrete composite structure, the premature damage to the RWS connections in the non-collapse stage will be improved.…”
Section: Calculation Methods Of the Seismic Fragilitymentioning
confidence: 99%
“…1, there are three common methods to improve the robustness of end plate steel connections [? ] by mobilising the plastic rotation from connection zone to a predefined location in the beam: strengthening the connection, reducing the beam section (RBS) and reducing the web section (RWS) [7]. These methods can be applied for retrofitting connections as well as in the design of new structures.…”
Section: Seismicmentioning
confidence: 99%